Gender Differences in Pediatric Orthopaedics: What Are the Implications for the Future Workforce? - Amoli, Marielle A. (Clin Orthop Relat Res, 2016)
BACKGROUND: Although the number of women in surgical specialties has increased dramatically over the past two decades, little research exists regarding how a surgeon’s gender impacts job selection and practice models. Because the number of women specializing in pediatric orthopaedics continues to increase, it is important to understand how one’s gender affects practice choices and how this may affect the future workforce. QUESTIONS/PURPOSES: (1) Among pediatric orthopaedic surgeons, is gender associated with choice of practice type (academic, private practice, hospital-based, solo)? (2) For men and women, what are the most common reasons for choosing a job? (3) For new graduates, do men and women have equal starting salaries? (4) Do men have a higher chance of getting job offers? (5) Is there a difference in workload (call frequency and surgical case volume) for men and women? (6) Finally, is there a difference in imminent retirement plans for men and women? METHODS: The 2015 Pediatric Orthopaedic Society of North American (POSNA) Needs Assessment Survey was sent to POSNA members and a special 36-question survey was sent to recent pediatric orthopaedic fellowship graduates. Both surveys included questions about self-reported gender, practice type, reasons for job selection, and call frequency. In addition, the new graduates’ survey also included questions about starting salary, job offers, and number of additional fellowships completed. Responses were analyzed by gender. Chi-square and Fisher’s exact tests assessed for statistical significance. RESULTS: Among the new graduates, women are more likely to choose academic practice (women: 13 of 18 [72%], men: 21 of 44 [48%], odds ratio [OR], 3.10 [confidence interval CI, 0.86–11.10], p < 0.001), whereas men are more likely to choose private practice (men: 14 of 44 [32‰], women: one of 18 [6%], OR, 0.12 [CI, 0.015–1.001], p < 0.001). The primary reasons for choosing a job were not different between men and women. Among the new graduates, geography/family considerations were reported as being highly important when selecting a job (men: 33 of 44 [75%], women: 16 of 18 [89%]) followed by academic opportunities (men: 24 of 44 [55%], women: 14 of 18 [78%]). Interestingly, a higher percentage of males reported finances as being important when selecting a job (men: 23 of 44 [52%], women: five of 18 [28%]). For the current POSNA members, the most important reasons when choosing a job for both men and women were quality of partners (men: 168 of 408 [41%], women: 66 of 122 [54%]) and an interesting practice (men: 155 of 408 [38%], women 54 of 122 [44%]. As a result of our small sample size, there was no difference in starting salaries between men and women (< USD 350,000: men 22 of 44 [50%], women 12 of 18 [67%]; USD 350,000-450,000: men 11 of 44 [25%], women six of 18 [33%]; > USD 450,000: men eight of 44 [18%], women zero of 18 [0%], p = 0.131). When stratified by practice type, for private practice starting salaries, over half of men (seven of 13 [54%]) placed in the highest category of > USD 400,000, whereas the single woman respondent placed in the lowest category of < USD 300,000. Men were more likely to report having job offers before starting their fellowship (men: 24 of 44 [54%], women: eight of 18 [44%], OR, 0.67 [CI, 0.22–2.0], p = 0.042). Finally, among POSNA members, women reported a lower weekly surgical case volume compared with men. Of the men, 108 of 408 (26%) reported performing more than seven surgeries per week compared with 12 of 122 women (10%; OR, 3.4 [CI, 1.8–6.44], p < 0.001). CONCLUSIONS: Although the numbers are small given the specialized nature of pediatric orthopaedic surgery, this study has uncovered some initial gender differences regarding practice characteristics and job opportunities among pediatric orthopaedic surgeons. As more men plan to reduce their workload or retire in the next 5 years, there may be further increases in the percentage of women surgeons in the workforce, so it is important that we begin to understand what effect, if any, gender has on practice patterns, job selection, and opportunities. Also, the finding that among the new graduates more women than men are choosing careers in academic practice over private practice suggests an extraordinary opportunity to develop more female leaders and role models at major pediatric orthopaedic centers.